Integrating digital analytics in strategic marketing decision making: An absorptive capacity approach - Kovala, Timo (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Over the last two decades, digital analytics has evolved from simply monitoring clicks to ever more complex campaign analyses and evaluations of marketing communication performance. However, the rapid rate of technological development has overshadowed the strategic importance of digital analytics for marketing practitioners and researchers alike. This has led to a situation, where the technical execution of digital analytics has become known relatively well but its practical benefits and purposes have been left without much attention. This research aims to breach this research gap by answering the question: how can companies integrate digital analytics in their strategic marketing decision making. This is a qualitative single case study, the focus of which is the company Unilever. The empirical data comprises eight semi-structured interviews as well as two digital analytics reports supplied by the case company. Literature on the absorptive capacity theory and strategic marketing decision making was used as a basis for the analysis of the data. The research findings suggest that it is possible to use digital analytics to generate strategically relevant knowledge on actual customer behaviour, wants and interests. The findings also indicate that digital analytics as a concept is broad and consists of several analytics subclasses, each with their distinctive characteristics and purposes. Furthermore, the findings highlight the challenges and obstacles that companies face in their attempts to integrate digital analytics in their strategic decision making processes. The main theoretical contribution of this study is to illuminate the strategic relevance of digital analytics. Digital analytics should not be viewed simply as a tool to monitor on-going marketing campaigns; in the right hands, it can generate valuable insights to support strategic marketing decision making. Another significant contribution is the conceptualisation of digital marketing knowledge. This research presents strong evidence to support the statement that the knowledge generated through digital analytics is fundamentally different from that of conventional consumer and market research. Companies can therefore use digital analytics to generate new insights on their customers, competitors and markets. In order to unleash this potential, companies must strive towards a flexible organisational structure and processes, offer purposeful employee training and support, develop a functional data management platform and be strategically committed towards developing their digital analytics capacity. Finally, this study provides research avenues for future research on the utility of digital analytics as a decision support tool. Further longitudinal analysis or a multiple case study on this research topic would work toward confirming, refuting or supplementing the results of this study.